The Stigma of disease and disability understanding causes and overcoming injustices (American Psychological Association, 2014)
The lives of people with disease and disability are harmed not only by their conditions but by public response to these conditions in the form of stigma and discrimination. Making sense of this injustice is the focus of this book. The two main sections of the book comprise chapters on 10 specific illnesses and conditions (mental illness, substance abuse, intellectual disability, physical and sensory disabilities, HIV-AIDS, infectious disease, cancer, obesity, childhood disorders, and Alzheimer's disease) and chapters relating to broader issues (stigma and family, overcoming stigma, stigma across cultures, and future directions). The book concludes with observations on what has not worked in overcoming stigma as well as possible future directions.